Africa - Ebbing Water, Surging Deficits : Urban Water Supply in Sub-Saharan Africa - Banerjee, Sudeshna (World Bank, Washington, DC, 2012)
With only 56 percent of the population enjoying access to safe water, Sub-Saharan Africa lags behind other regions in terms of access to improved water sources. Based on present trends, it appears that the region is unlikely to meet the target of 75 percent access to improved water by 2015, as specified in the Millennium Development Goals (MDG). The welfare implications of safe water cannot be overstated. The estimated health and time-saving benefits of meeting the MDG goal are about 11 times as high as the associated costs. Monitoring the progress of infrastructure sectors such as water supply has been a significant by-product of the MDG, and serious attention and funding have been devoted in recent years to developing systems for monitoring and evaluating in developing countries. Piped water reaches more urban Africans than any other form of water supply-but not as large a share as it did in the early 1990s. The most recent available data for 32 countries suggests that some 39 percent of the urban population of Sub-Saharan Africa is connected to a piped network, compared with 50 percent in the early 1990s. Analysis suggests that the majority of those who lack access to utility water live too far away from the distribution network, although some fail to connect even when they live close by. Water-sector institutions follow no consistent pattern in Sub-Saharan Africa. Where service is centralized, a significant minority has chosen to combine power and water services into a single national multi-utility urban water sector reforms were carried out in the 1990s, with the aim of creating commercially oriented utilities and bringing the sector under formal regulation. One goal of the reforms was to attract private participation in the sector.